Implementasi Program Sertifikasi Guru dalam Peningkatan Mutu Pendidikan ( Study Kasus di Kabupaten Aceh Utara ) - Nurhafni Nurhafni (Magister Ilmu Administrasi Publik, 2010)
Law No 14/ 2005 on teacher certification is one of the efforts to the government to enhance professionalism of teachers. However, the reality is that the implementation of the program in NAD province has face many obstacles. One of the factor, is the condition on the ground in the wake of the conflict and tsunami disaster, which is still characterized by multiplicity of crises. Findings of the study indicate that teacher certification program has shifted in value. First is initial goal was to increase teacher’s professional development, but today, the objective has shifted to increasing teacher’s welfare. To that end, the main objective of teacher certification program has not been achieved. Thus, the existence of teacher certification program does not have any influence on teacher quality. Moreover, the law on teacher certification, has in part been influenced by political vested interests, which is the why the program is not based on god political will of the government to increase teacher professionalism.